Genome-wide association analysis of wheat stem traits using 55K microarrays - Wang, Wei; Sun, Na; Zhao, Kai; Song, JiKun; Fang, Hui; Fan, Guiqiang; Gao, Yonghong; Huang, Tianrong; Ding, Yindeng (Frontiers in Plant Science, 2025)
Wheat lodging poses a severe threat to yield and quality, with the morphological and structural traits of the basal second internode being critical determinants of stem strength and lodging resistance. We conducted phenotypic analysis on 239 wheat varieties (lines) collected from around the world. This analysis was complemented by genotyping using the wheat 55K SNP chip. Genome-wide association analysis (GWAS) was executed employing the MLM (Q+K) algorithm within the TASSLE software suite. The findings unveiled pronounced phenotypic variability in the stem diameter of the second internode across disparate temporal intervals, characterized by a coefficient of variation spanning from 11.31% to 13.95%, alongside robust inter-year correlations. Furthermore, the genome-wide linkage disequilibrium (LD) decay distance was ascertained to 3 Mb. Analyses of population structure, phylogenetic dendrograms, and principal components revealed that the intrinsic population structure of the 239 wheat varieties (lines) was markedly simplified, segregating into three discernible subgroups. GWAS analysis identified 118 SNPs significantly associated with the stem diameter of the second internode (P ≤ 0.001). Notably, among these loci, three SNPs (AX-111557672, AX-94584919, and AX-109819835) overlapped with previously reported associations, while the remaining 115 SNPs represented novel discoveries distributed across chromosomes 1A, 1B, 1D, 2A, 2B, 2D, 3A, 3B, 4A, 4B, 4D, 5A, 5B, 6A, 6B, 6D, 7A, 7B, and 7D. These newly identified loci exhibited substantial phenotypic variance explained, ranging from 8.09% to 29.14% for individual SNPs. Subsequent rigorous screening of loci showing significant phenotypic impacts and stability across diverse environmental contexts culminated in the identification of seven candidate genes implicated in the stem diameter of the second internode. This investigation provides new SNPs markers for enhancing lodging resistance in wheat, highlighting substantial practical implications.